1984
DOI: 10.1002/cm.970040105
|View full text |Cite
|
Sign up to set email alerts
|

Microfilament rearrangements during fibroblast‐induced contraction of three‐dimensional hydrated collagen gels

Abstract: In vitro models have been developed recently to study the ability of fibroblasts to generate tensile force within collagen gels. The present study was initiated to assess the role of the cytoskeleton in the cell shape changes and force generation in one such model system. Porcine periodontal ligament fibroblasts ( PPLF ) were cultured within three-dimensional collagen gels attached to glass coverslips. Fluorescence microscopy, using nitrobenzooxadizole (NBD)- phallacidin labeling for microfilaments and tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…The experimental system that we developed has several advantages, including the availability of a commercially prepared collagen; the rapid, reproducible extent of contraction; the well-defined gel composition; and the easily measured and reproducible end point. The collagen concentration used in this model, which is lower, and the cell number, which is higher, than those previously reported using fibroblasts (8,27), permit the determination of gel contraction within 24 hr.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The experimental system that we developed has several advantages, including the availability of a commercially prepared collagen; the rapid, reproducible extent of contraction; the well-defined gel composition; and the easily measured and reproducible end point. The collagen concentration used in this model, which is lower, and the cell number, which is higher, than those previously reported using fibroblasts (8,27), permit the determination of gel contraction within 24 hr.…”
Section: Discussionmentioning
confidence: 73%
“…Specifically, IEC-6 cells, a rat intestinal crypt cell line (3), require binding to laminin for organization into multicellular epithelial sheets (4). Tractional forces generated by cells play critical roles in both embryogenesis (5,6) and wound healing (7,8). Fibroblasts grown on type I collagen gels extensively modify the collagen gels (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In marked contrast, cells in anchored matrices become bipolar and orient along lines of tension (Stopak and Harris, 1982;Bellows et al, 1982). Cells develop prominent stress fibers and fibronexus junctions and resemble myofibroblasts (Farsi and Aubin, 1984;Mochitate et al, 1991;Tomasek et al, 1992). Therefore, fibroblasts can contract a tissue matrix in vitro without differentiating into myofibroblasts, and the appearance of myofibroblasts correlates with development of stress in the matrix.…”
Section: Collagen Matrix Contraction and The Cell Phenotypementioning
confidence: 99%
“…The main reasons for which BNNT was chosen are: (i) excellent elastic modulus (750-1200 GPa [134][135]), (ii) excellent tensile strength (>24 GPa [136]), similar range to CNT, and (iii) positive reports on its biocompatibility [137][138][139][140][141]. It is emphasized that no study existed on HA-BNNT composite before the work reported in this dissertation.…”
Section: Boron Nitride Nanotube: Alternative To Carbon Nanotubementioning
confidence: 99%